2010
DOI: 10.1586/erp.10.72
|View full text |Cite
|
Sign up to set email alerts
|

Comparing policies to enhance prescribing efficiency in Europe through increasing generic utilization: changes seen and global implications

Abstract: This cross-national study has demonstrated considerable variation in the utilization and expenditure of PPIs and statins across Europe, providing opportunities to further improve prescribing efficiency. The '4 Es' do provide an understandable methodology to document and compare the influence of different demand-side measures, with the influence varying by their extent and intensity. Further reforms are essential given current financial pressures. Consequently, further research will concentrate on the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
247
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(271 citation statements)
references
References 55 publications
23
247
0
1
Order By: Relevance
“…These are in addition to compulsory price cuts for both originators and generics instigated among some European countries as they struggle to contain rising pharmaceutical expenditure [1,3,5,8,9].…”
Section: Pr Icin G Policies To H Elp Low Er Th E Pr Ice Of Gen Er Icsmentioning
confidence: 99%
See 3 more Smart Citations
“…These are in addition to compulsory price cuts for both originators and generics instigated among some European countries as they struggle to contain rising pharmaceutical expenditure [1,3,5,8,9].…”
Section: Pr Icin G Policies To H Elp Low Er Th E Pr Ice Of Gen Er Icsmentioning
confidence: 99%
“…However, the general trend is for countries to introduce additional measures to lower their generics prices to maximise savings with countries continuing to learn from each other [3,5,8], introducing initiatives highlighted in Table 1. For instance, high volume generics in Sweden and UK are priced at between 3-13% of pre-patent loss prices through a variety of market force measures, some of which are highlighted in Table 2 [3,7,14,21].…”
Section: Pr Icin G Policies To H Elp Low Er Th E Pr Ice Of Gen Er Icsmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare professionals are concerned about switching between asthma drugs because it may negatively affect disease control through low adherence, and incorrect use of aerosol delivery device types [3,8]. In literature, there is evidence that switching has a negative impact on adherence and disease control through changes in color, size, and packaging [9][10][11][12]. Data from a questionnaire study showed that patients who switched asthma medication, more often experienced difficulties using the device (23% vs. 13%), were less likely to be adherent (55% vs. 68%) and were less likely to report being asthma controlled (69% vs. 83%) compared to patients who did not switch [13].…”
Section: Introductionmentioning
confidence: 99%